Kidnapped and Catriona - Stevenson, Robert Louis; Edited with an Introduction and Notes by Emma Letley (Oxford, New York Oxford University Press, 2000)
A sixteen-year-old orphan is kidnapped by his villainous uncle, but later escapes and becomes involved in the struggle of the Scottish highlanders against English rule.
Include Map, Glossary, Bibliography and Notes
Keywords: Scotland -- Kidnapping -- English language